Finding the inverse for two variable functions

functionsinverseinverse function

so I have this function:
$$f(x,y) = (ax+by, cx+dy)$$

I was wondering how you would find the inverse for this function. I know it is defined to $$f^{-1}(x,y)=\biggl(\frac{dx-by}{ad-bc}, \frac{-cx+ay}{ad-bc}\biggr)$$ when $ad-bc\neq0$ but I have no idea how this was calculated or solved other than it being written within the solution manual of a problem that involves taking the inverse. Some help would be appreciated.

Best Answer

In general, finding a formula for the inverse of a 2-var function can be very very hard. For the specific case of a function like this one ("linear in each variable") we can do it with basic algebra. Write \begin{align} u &= ax + by\\ v &= cx + dy. \end{align} The goal is then to find expressions for $x$ and $y$ just in terms of $u$ and $v$.

Multiply the top equation by $d$ and the bottom by $b$ to make the $y$ terms the same: \begin{align} du &= adx + bdy\\ bv &= bcx + bdy. \end{align} Subtract the top equation from the bottom to get \begin{align} du &= adx + bdy\\ bv - du &= bcx - adx = (bc - ad)x. \end{align} And now you can solve that last equation for $x$, getting \begin{align} du &= adx + bdy\\ \frac{bv - du}{bc - ad} &= x. \end{align} You can either plug that into the first equation and solve for $y$, or you can return to the start and multiply the top equation by $c$ and the bottom by $a$ to get \begin{align} cu &= acx + bcy\\ av &= acx + ady. \end{align} Subtract to get \begin{align} cu &= acx + bcy\\ av - cu &= ady - bcy = (ad - bc)y \end{align} and then divide the last equation to get \begin{align} \frac{av - cu}{ad - bc} &= y \end{align}

and there are your two formula!

Related Question